National and Provincial Estimates of Catastrophic Health Expenditure and its Determinants in Nepal - Thapa, Arjun Kumar; Pandey, Achyut Raj (Journal of Nepal Health Research Council, 2021)
Background: Despite various supply-side efforts, out of pocket expenditure occupies a considerable portion of healthcare financing in Nepal. With the recent process of federalization in country, there is additional scope for contextualized planning at provincial level to prevent catastrophic health expenditure among Nepalese households. In this context, this study intends to estimate the proportion of population facing catastrophic health expenditure at national and provincial level and identify the determinants of catastrophic health expenditure. Methods: This study involved analysis of Nepal Living Standard Survey III, which was a cross sectional study. Out of 5,988 households comprising 28,460 individuals, data from total of 7,911 individuals who reported having acute or chronic illness was extracted and analyzed in the study. Results: In the study, 11.11% of households had faced catastrophic health expenditure. Catastrophic health expenditure was found to be 11.3% in Province 1, 9.4% in Province 2, 10.7% in Bagmati Province, 10% in Gandaki Province, 11.7% in Lumbini Province, 13.3% in Karnali Province and 13.4% in Sudurpaschim Province. Household size, literacy status of household head, consumption quintile, urban or rural residence, type of illness and type of health facility visited were identified as determinants of catastrophic health expenditure. Conclusions: A tenth of households, most of whom lying below poverty line, residing in rural areas, suffering from chronic illness are facing catastrophic healthcare burden. The government needs to pursue its equity-oriented strategies preventing catastrophic health expenditure and impoverishment associated with it. Keywords: Catastrophic health expenditure; out of pocket payment; Nepal